2010
DOI: 10.3233/jad-2010-100234
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Fiber Tract Integrity in Healthy Aging and Mild Cognitive Impairment: A DTI Follow-Up Study

Abstract: Cross-sectional studies using diffusion tensor imaging (DTI) suggest decline of the integrity of intracortically projecting fiber tracts with aging and in neurodegenerative diseases, such as Alzheimer's disease (AD). Longitudinal studies on the change of fiber tract integrity in normal and pathological aging are still rare. Here, we prospectively studied 11 healthy elderly subjects and 14 subjects with amnestic mild cognitive impairment (MCI), a clinical risk group for AD, using high-resolution DTI and MRI at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
101
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(113 citation statements)
references
References 0 publications
12
101
0
Order By: Relevance
“…80 The more pronounced damage of inferior fronto-occipital and inferior longitudinal fasciculi in md-aMCI compared with sd-fMCI is in agreement with the retrogenesis hypothesis in AD that postulates an early involvement of late-myelinating pathways in the initial phases of the degenerative process. 29,31 The comparison between sd-fMCI and sd-aMCI yielded no significant group differences. There are 2 possible explanations for this result.…”
Section: Tbss Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…80 The more pronounced damage of inferior fronto-occipital and inferior longitudinal fasciculi in md-aMCI compared with sd-fMCI is in agreement with the retrogenesis hypothesis in AD that postulates an early involvement of late-myelinating pathways in the initial phases of the degenerative process. 29,31 The comparison between sd-fMCI and sd-aMCI yielded no significant group differences. There are 2 possible explanations for this result.…”
Section: Tbss Analysismentioning
confidence: 99%
“…Most investigations included only 1 (not further specified) MCI group, [23][24][25] or only the sd-aMCI subtype, [26][27][28][29] or a mix of several subtypes, with the aim of discriminating stable versus progressive MCI. 30 Only 3 recent contributions compared DTI patterns in aMCI versus non-MCI.…”
Section: Tbss Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…79 In a longitudinal study, in 62 CADASIL subjects the changes in mean diffusivity correlated with changes in the Rankin score, national institute of health stroke scale and structured interview for the diagnosis of dementia of the Alzheimer type, multiinfarct dementia and dementias of other aetiology within a 2-year observation period. 28 Diffusion tensor imaging was also used in early detection 80,81 and monitoring of disease progression from mild cognitive impairment to Alzheimer's disease. 82 Sample size calculation based on 2-year follow-up data in CADASIL patients showed that one would need 1,944 subjects per treatment arm to show a treatment effect of 20% with an 80% power when mean diffusivity is used as the trial outcome.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%
“…A previous rsfMRI study has demonstrated that decreased interhemispheric functional connectivity in sensorimotor cortex, superior temporal gyrus, and superior parietal lobule was relevant to functional defects in autism patients (Anderson et al, 2011). A decline of anterior white matter integrity was also found in elderly people with cognitive impairment (Teipel et al, 2010). Such cognitive disorders could be associated with the abnormal transcallosal connectivity in the relevant cortical regions.…”
Section: Discussionmentioning
confidence: 93%